Diabetic kidney disease in northwest Ethiopia: Prevalence and determinants among adults with type 2 diabetes - Workagegnehu Hailu; Tadesse Asmamaw Dejene; Markeshaw Tiruneh; Meseret Derbew Molla; Eshetie Melese Birru; Shitaye Alemu; Tadesse Awoke (PLoS ONE, 2026)
Background Diabetic kidney disease (DKD), mainly due to type 2 diabetes (T2DM) is the leading cause of end-stage kidney disease globally. However, DKD prevalence in sub-Saharan Africa, particularly Ethiopia, is underexplored, especially using reliable markers like quantified albuminuria and cystatin C based estimated glomerular equations (eGFR). This study aimed to assess DKD prevalence and associated factors using multiple diagnostic markers. Methods A cross-sectional study was conducted in adult T2DM patients at the University of Gondar Comprehensive Specialized Hospital using systematic random sampling. Data on socio-demographics and lab parameters were collected, with DKD diagnosed via eGFR and/or albuminuria (spot urine albumin-to-creatinine ratio and 24-hour collection). SPSS version 28 was used for data analysis, and factors were identified through multivariable logistic regression, with significance at 95% CI and p < 0.05. Results In a study of 204 T2DM patients (mean age 60.2 years; 57.4% female), the prevalence of DKD was 37.3% (95% CI: 30.6–44.3). Significant factors associated with DKD included urban residence (AOR = 0.278, p = 0.023), poor blood pressure control (AOR = 2.33, p = 0.016), poor glycemic control (AOR = 2.93, p = 0.007), and longer diabetes duration (AOR = 6.78, p < 0.0001). Conclusion This study shows a high prevalence of DKD in T2DM patients, mainly identified via albuminuria. Poor blood pressure control, inadequate glycemic control, and longer diabetes duration were significantly associated with DKD. Regular screening and improved glycemic and blood pressure control are essential to slow DKD progression.